Cryptorchidism in the Karagouniko breed of sheep and its economic consequences - LAINAS (Θ. ΛΑΪΝΑΣ) Th.; DELIGIANNIS (Κ. ΔΕΛΗΓΙΑΝΝΗΣ) K. (Journal of the Hellenic Veterinary Medical Society, 2018)
The aim of the present study was to evaluate the frequency of cryptorchidism in the Karagouniko breed of sheep. The animals used were derived from the sheep flock at the Agricultural Research Station of Palamas (Karditsa), consisting of 500 breeding ewes and 15 rams of the Karagouniko breed and from two hundred and seven flocks of Karagouniko breed genetic nucleus. In addition 14.107 carcasses of Karagouniko male lambs, slaughtered at the abattoir of Karditsa and the size and weight of testicles and epididymides of 18 cryptorchidic and 7 normal lambs were examined. Finally, the economic impact of this defect was also evaluated. The results showed that cryptorchidism is a defect with a high frequency (23.81% of male lambs, P<0.001) in the Karagouniko breed and it is associated with polledness. The frequency of cryptorchidism is increased in sheep flocks where inbreeding is applied. Cryptorchidism was found to be bilateral or unilateral (20:1 respectively, P<0.001). The most common type of unilateral defect was found to be the right one (10:1, P<0.001). Bilateral was of abdominal or inguinal type(400:l,P<0.001). Testicular aplasia was found to be rare (0.02% of total examined male lambs or 0.09% of cryptorchid ones). The weight of "hidden" testicles and epididymides was lower than that of normal (-14.06% and -22.99% respectively, P<0.001). However, until the age of 4 months, there was no difference in weight between cryptorchidic and normal lambs. Males with bilateral cryptorhidism were not able to produce semen. Cryptorchidism causes a considerable decrease in sheep breeders’ income (P<0.001), as it deprives them of the opportunity to sell male lambs as breeding animals at the higher than usual price. It is concluded that the high frequency of cryptorchidism in the Karagouniko sheep significantly retards the genetic improvement of the breed and decreases the farmer’s income.